Theoretical aspects and applications of goal-oriented reanalysis methods - Materna, Daniel (Proceedings in applied mathematics and mechanics : PAMM)
Abstract In this contribution, a method for goal-oriented reanalysis is presented. The process allows predicting the change in a quantity of interest due to structural modifications (design changes), for example, the shape, the topology, material properties, and so forth. The approach is based on a goal-oriented method using primal and dual problems. Furthermore, the procedure is easy to implement in existing finite element programs because no derivatives with respect to the design variables are necessary. The proposed method can be used in classical applications with successive design steps, such as structural optimization, reliability, or structural damage analysis. The repeated structural analysis and calculating quantities of interest involve significant computational effort. Goal-oriented reanalysis methods can reduce the overall computational cost in the numerical simulation.